Reflection in motion: an embodied approach to reflection on practice. Issue 2 (4th March 2021) - Botelho, Natashia
ABSTRACT: Body Phenomenology is introduced as a framework for deepening critical reflection on practice by attending to the active engagement between the practitioner and their world. Fook's Critical Reflection on Practice is outlined as an established model of critical reflection that misses the role of the body in reflection. This is followed by an introduction to body phenomenology through Merleau-Ponty's philosophy of embodiment, motility and experience. Conceptions of embodiment are examined to highlight the dynamics of human experience through body-world relations. It is argued that using the body to reflect on life and experience can offer enhanced critical insight on practice and support deeper consciousness regarding one's manner of knowing, relating, and moving through situations. The paper ends with a call for practitioners and students to consider incorporating body phenomenology into their reflective processes to gain rich personal and practice insights through embodied reflection in movement.